Antioxidant biomarkers and cardiometabolic risk markers in an Aboriginal community in remote Australia: a cross-sectional study. Issue 15 (2nd October 2021) - Knudsen, Lenette; Lyons, Jasmine G; O'Dea, Kerin; Christensen, Dirk L; Brimblecombe, Julie K
Abstract: Objective: High-quality diets, characterised by nutrient-rich foods, are one of the foundations for health and well-being. Indicators of diet quality, antioxidants, are associated with protection against cardiometabolic diseases. The current study explores relationships between plasma antioxidants and cardiometabolic risk among Aboriginal people in Australia. Design: As part of a community-driven health promotion programme, we conducted a cross-sectional study including a health-behaviour questionnaire, plasma antioxidants and cardiometabolic risk markers (anthropometric, blood pressure measurements, fasting glucose, glycated Hb (HbA1c ), lipids, C-reactive protein and albumin-creatinine-ratio) continuous and categorised into population-specific cut-offs. Antioxidants ( β -carotene, β -cryptoxanthin, lycopene, lutein-zeaxanthin, retinol and α -tocopherol measured using HPLC) were applied to a principal component analysis, which aggregated these into a single component. Linear regression models were applied to investigate associations between the antioxidant component and cardiometabolic risk markers. Setting: Community in a remote area in Northern Territory, Australia. Participants: A total of 324 Aboriginal people, mean age 35·5 (range 15–75) years. Results: Antioxidant component levels were higher among individuals with higher self-reported vegetable intake ( P < 0·01), higher among individuals with higher self-reported fruit intake ( P = 0·05) and lower among current smokers ( P = 0·06). Linear regression revealed an inverse association between the antioxidant component and C-reactive protein ( β = –0·01, P < 0·01) after adjusting for confounders. Conclusion: Higher plasma antioxidant levels, indicators of diet quality, were associated with lower levels of high-sensitivity C-reactive protein in this Aboriginal population in remote Australia. This association suggests plasma antioxidants may be protective against inflammation; however, longitudinal studies are needed to examine this potentially protective relationship.